Analisis SWOT Manajemen Mutu Terpadu Pendidikan pada MAN 1 Mandailing Natal - Reni Septrisia; Aldy Atillah Lubis; Nanda Fitriani; Syarifah Syarifah; Siti Asiyah; Anisah Lubis; Eva Suryani (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to explain or describe integrated education quality management planning using a SWOT analysis at MAN 1 Mandailing Natal. This research uses a descriptive method with a qualitative approach. The research was conducted by direct interviews with the main respondent, namely the Deputy Head of Madrasah MAN 1 Mandailing Natal in the Curriculum Sector. Data was collected through observation, interviews and documentation, including the use of the madarasah's social media to seek additional information related to the matter under study. This research found that the integrated education quality management planning at MAN 1 Mandailing Natal involved all parties in the organization, from leaders, staff and teaching staff who formulated the vision, mission and goals of the madrasa. The SWOT analysis of integrated quality management planning at MAN 1 Mandailing Natal serves to determine the strengths, weaknesses, opportunities and threats that will be faced by MAN 1 Mandailing Natal in planning an integrated education quality management. Effective integrated quality management will improve the quality of an educational institution, and produce graduates who are academically and non-academicly competent.